PENGARUH SUDUT KELENGKUNGAN SUDU SAVONIUS PADA HORIZONTAL AXIS WATER TURBINE DI ALIRAN DALAM PIPA - Taufan Apha Sanditya; Syamsul Hadi; D. Danardono Dwi Prija Tjahjana (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
Water turbine is a device that works to convert water energy into mechanical energy in the form of a torque in turbine shaft. In this study, the angle of attack of Savonius water turbine with horizontal axis (HAWT), simulated using “Solidworks Flow Simulation” software, is obtained by applying the model in a flow through a pipe. The angle of attack used in this simulation is varied from 110°, 120°, 130° and 140°. The aims of this research are to obtain the optimum angle of attack with a debit of 0,0122 m3/s. Then the angle of attack of the blade is evaluated based on the torque, pressure contour and fluid velocity distribution. The results show that the optimum angle of attack is found at 120° with the torque about 3,8 Nm. Keywords: picohydro, angle of attack, solidwork, savonius, torque